Association Between FTO rs9939609 Polymorphism and Nutritional Status in Adults With Different Metabolic Phenotypes - Sierra-Ruelas, Erika; Vizmanos-Lamotte, Barbara; Martínez-López, Erika; Campos-Pérez, Wendy (Current developments in nutrition, 2021)
Analyze the association between FTO rs9939609 polymorphism and nutritional status in Mexican adults with metabolically healthy or unhealthy phenotype. 266 Mexican adults with normal/excess weight (NW/EW) were included. Anthropometric, biochemical, and dietary parameters were determined. The subjects were classified into two metabolic phenotypes: healthy/unhealthy phenotype (MHP/MUHP). The subject’s classification used the homeostatic model assessment insulin resistance (HOMA-IR) and cut-off points from NCEP-ATP III for glucose, triglycerides (Ty), high-density lipoprotein cholesterol, and blood pressure. Subjects with ≤1 altered parameter were classified as MHP. The genotypes TT/TA/AA were identified by allelic discrimination with TaqMan® probes. Among the subjects with NW, 30% had the MUHP compared to 61% of the subjects with EW. The 55.3% presented the TT genotype, 30.3% AT, and 6.4% AA. Subjects with NW and MHP have greater parameters in the TT genotype (vs AT/AA, respectively): Ty (97.7 ± 30 mg/dL vs 80.6 ± 27.6 mg/dL, p = 0.008), very low density lipoprotein cholesterol (VLDL-C) (19.5 ± 6 mg/dL vs 16.1 ± 5.6 mg/dL, p = 0.008), Ty/glucose (TyG) index (3.6 ± 0.1 vs 3.5 ± 0.1, p = 0.022) and in men, the Ty/HDL-C (2.5 ± 0.8 vs 1.5 ± 0.5, p = 0.010). Subjects with NW and MUHP, HOMA-IR (TT, 2.7 ± 2.4 vs AT/AA, 3.9 ± 2.2 p = 0.011) and protein intake (TT, 18.1 ± 0.9 vs AT/AA, 15.3 ± 0.9% p = 0.043) showed significant differences. Moreover, subjects with EW and MHP have higher parameters in AT/AA genotype (vs TT, respectively): body mass index (BMI) (29.9 ± 4.2 vs 27.8 ± 2.2 kg/m2, p = 0.015), muscle mass (12.9 ± 2.4 vs 11.3 ± 1.9 kg, p = 0.028), total cholesterol (193.6 ± 33.1 vs 167.2 ± 35.9 mg/dL, p = 0.013), low density lipoprotein cholesterol (LDL-C) (121.1 ± 33.4 vs 100.7 ± 32.2 mg/dL p = 0.040) and TyG index (3.6 ± 0.1 vs 3.5 ± 0.1, p = 0.033). In subjects with EW and MUHP significant differences were found between AT/AA vs TT genotype, respectively, in insulin (19 ± 9.7 vs 13.8 ± 6.6 μU/ml, p = 0.006) and HOMA-IR (4.5 ± 2.4 vs 3.3 ± 1.7, p = 0.016). In subjects with NW and TT genotype, higher levels in Ty, VLDL-C, TyG index, and Ty/HDL index were found. In subjects with EW and AT/AA genotype, higher values in BMI, muscle mass, total cholesterol, VLDL-C, TyG index, insulin, and HOMA-IR were reported. This work was supported by FODECIJAL, PRO-SNI, and PROINPEP.